Chemistry, transport, emission, and shading effects on NO2 and Ox distributions within urban canyons. (15th December 2022) - Dai, Yuqing; Cai, Xiaoming; Zhong, Jian; Mazzeo, Andrea; MacKenzie, A. Rob
Abstract: The capacity to predict NO2 and the total oxidant (Ox = NO2 + O3 ) within street canyons is critical for the assessment of air quality regulations aimed at enhancing human wellbeing in urban hotspots. However, such assessment requires the coupling of numerous processes at the street-scale, such as vehicular emissions and tightly coupled transport and photochemical processes. Photochemistry, in particular, is often ignored, heavily simplified, or parameterized. In this study, MBM-FleX — a process-based street canyon model that allows fast computation of various emission profiles and sun-lit conditions with tightly coupled physical (transport and mixing) and chemical processes and without loss of sufficient spatial resolution — was used to simulate shading effects on reactive species within urban canyons. Driven by pre-generated large-eddy simulation of flow, MBM-FleX results show that shading effects on volatile organic compound (VOC) free-radicals significantly affect the interconversion of odd-oxygen species that cannot be captured by the simple NOx -O3 chemistry, for example, reducing NO2 by limiting the formation of hydroperoxyl radicals. Consistent with previous results in simpler model systems, the inclusion of VOC free-radical chemistry did not appreciably alter the sensitivity of NO2 to shading intensity in regular canyons, but a non-linear relationship between NO2 and shading intensity is found in deep canyons when the air residence time grew. When solar incidence simultaneously passes through multiple vortices in street canyons, VOC chemistry and shade may considerably influence model results, which may therefore affect the development of urban planning strategies and personal exposure evaluation. Graphical abstract: Image 1 Highlights: 2D chemistry simulates shading effects on air pollution in urban street canyons. Shading changes pollutant spatial patterns in urban canyons through chemistry. Shading can decrease NO2 when VOC free-radical chemistry is involved. Ox conservation does not hold for shading combined with VOC chemistry.